Can high social capital at the workplace buffer against stress and musculoskeletal pain?: Cross-sectional study. Issue 12 (March 2018) - Jay, Kenneth; Andersen, Lars L.
Abstract : Abstract: Work-related musculoskeletal pain and stress are both highly prevalent in the working environment and relate well to the biopsychosocial model. While the onset of musculoskeletal pain is often dependent on the biological element of the biopsychosocial model, chronic pain is often influenced by psychological and social factors. Similarly, stress is also influenced by biological, psychological, and social factors. This study investigates the possibility of social capital being a buffer for stress and musculoskeletal pain in a group of female laboratory technicians. Female laboratory technicians (n = 500) replied to questions about stress (Cohens Perceived Stress Scale-10), musculoskeletal pain (0–10 visual analog scale), and social capital at the workplace (bonding [in teams], bridging [between teams], and linking [between teams and leaders]). Outcome variables were stress and musculoskeletal pain and the predictor variable was social capital. General linear models tested the association of the 3 types of social capital (predictor variables) with stress and pain (mutually adjusted outcome variables). Analyses were controlled for age, lifestyle (body mass index, smoking), seniority, and working hours per week. For stress as outcome, moderate and high bonding social capital were different from low social capital with −2.04 (95% confidence interval [CI] −3.33 to −0.76) and −4.56 (95% CI −5.84 to −3.28) points on the Perceived Stress Scale of 0 to 42, respectively. Similarly, moderate and high bridging social capital were different from low social capital with −1.50 (95% CI −2.76 to −0.24) and −4.39 (95% CI −5.75 to −3.03), respectively. For linking, only high social was significantly different from low with −2.94 (95% CI −4.28 to −1.60). None of the 3 types of social capital was associated with musculoskeletal pain. Higher levels of social capital at the workplace appear to buffer against stress, but not against musculoskeletal pain. Intervention studies should investigate whether improving bonding, bridging, and linking social capital at the workplace may be a viable strategy to prevent or reduce work-related stress.